Multiple factors regulate the expression of sufCDSUB in Streptococcus mutans - Ellepola, Kassapa; Guillot, Lauren C.; Comeaux, Bradley; Han, Yiran; Kajfasz, Jessica K.; Bitoun, Jacob P.; Spatafora, Grace; Lemos, Jose A.; Wen, Zezhang T. (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionThe sufCDSUB gene cluster, encoding the sole iron-sulfur (Fe-S) cluster assembly system in S. mutans, was recently shown to be up-regulated in response to oxidative stressors and Fe limitation.MethodsIn this study, luciferase reporter fusion assays, electrophoretic gel mobility shift assays (EMSA) and in vitro transcription assays (IVT) were used to dissect the cis- and trans-acting factors that regulate the expression of sufCDSUB.Results and discussionResults showed deletion of perR, for the only Fur-family transcriptional regulator in S. mutans, resulted in >5-fold increases in luciferase activity under the control of the sufCDSUB promoter (P<0.01), as compared to the parent strain, UA159 when the reporter strains were grown in medium with no supplemental iron. Site-directed mutagenesis of a PerR-box in the promoter region led to elevation of the reporter activity by >1.6-fold (P<0.01). In an EMSA, recombinant PerR (rPerR) was shown to bind to the cognate sufCDSUB promoter leading to mobility retardation. On the other hand, the reporter activity was increased by >84-fold (P<0.001) in response to the addition of cysteine at 4 mM to the culture medium. Deletion of cysR, for a LysR-type of transcriptional regulator, led to reduction of the reporter activity by >11.6-fold (P<0.001). Addition of recombinant CysR (rCysR) to an EMSA caused mobility shift of the sufCDSUB promoter probe, indicative of rCysR-promoter interaction, and rCysR was shown to enhance sufC transcription under the direction of sufCDSUB promoter in vitro. These results suggest that multiple factors are involved in the regulation of sufCDSUB expression in response to environmental cues, including cysteine and Fe availability, consistent with the important role of sufCDSUB in S. mutans physiology.